Knowledge translation: The Development, Evaluation, and Follow-up of Online and In-person Do-Live-Well Workshops for Occupational Therapists - Kim, Sungha (My University, 2021)
This dissertation presents knowledge translation processes regarding the Do-Live-Well (DLW) framework for Canadian occupational therapists (OTs) and consists of five chapters. The first chapter explains why this DLW educational research was needed and provides a description of the theoretical frameworks used in the DLW educational project, including knowledge translation, program evaluation, and adult education frameworks. In chapter 2, I described the process of developing the equivalent online and in-person educational workshops that were evidence- and theory-based. Three phases were undertaken to develop the DLW workshops: (1) understand DLW training needs, (2) develop educational content and apply the problem-based learning approach, and (3) conduct a usability test of the online workshop website. The findings from each phase were used in DLW online and in-person workshops. In chapter 3, findings of a mixed-methods study are presented. The study was designed to (1) compare the effectiveness of online education with in-person learning regarding the DLW framework for Canadian OTs and (2) further explore workshop participants’ experience in both learning formats. While there were no statistically significant differences in knowledge gained, the in-person group was more satisfied with their learning. Participants in both groups valued the importance of personal interactions in learning; the online learners said online learning did not provide the same quality of in-person interactions that in-person education provided. In chapter 4, I explored workshop participants’ experiences of using the DLW framework in practice three months after DLW workshops by asking about benefits, facilitators, and barriers of using the DLW framework in practice. Participants valued the importance of the DLW framework, but there were challenges of using the DLW framework, associated with structural, organizational, provider, innovation, and patient factors. In chapter 5, the contributions of the DLW educational project are discussed by providing insights related to knowledge translation using Knowledge-To-Action cycle.
Keywords: Occupational therapy; Continuing education; Health promotion; Online learning